Air Stability and Interfacial Compatibility of Sulfide Solid Electrolytes for Solid‐State Lithium Batteries: Advances and Perspectives. Issue 5 (1st February 2022) - Cai, Yinghui; Li, Chunli; Zhao, Zhikun; Mu, Daobin; Wu, Borong
Abstract: Sulfide solid electrolytes (SSEs) possess higher ionic conductivity compared to commonly used oxide electrolytes, and are expected to enable high‐safety, high‐energy‐density solid‐state batteries. However, the air sensitivity and interface instability of SSEs greatly limit their applications. Herein, research on the stability of SSEs is reviewed. The mechanisms for the air and interface instability of the SSEs are revealed. In addition, methods to improve the stability of SSEs are discussed. The air stability of SSEs is closely related to their structures, which can be modified by chemical or physical interactions to tackle the problem. Interface instability induced by physical contact, interface side reactions, and other issues between SSEs and electrodes is another problem, hindering their commercialization. An in‐depth understanding of SSEs is offered as well as the prospects of SSEs. Abstract : Sulfide solid electrolytes : The latest research advances for the air stability of sulfide solid electrolytes including intrinsic causes and corresponding chemical/physical modifications are discussed and evaluated in detail. Moreover, the reasons for cathode/anode interface instability such as poor interface contact, side reaction, space charge layer, as well as corresponding improvement strategies are systemically analyzed. The future development prospects of sulfide solid electrolytes are also provided.